The Influence of Teachers’ Profesisional Competences on the Reading Writing and Arithmetic Ability of Grade 3 Students at MI Ta’Mirul Islam Surakarta - Annisa Putri Utami; Lailla Hidayatul Amin; Alfian Eko Rochmawan (Universitas Muhammadiyah Enrekang, 2024)
This study aims to examine the influence of teacher professional competence on the reading, writing, and arithmetic abilities of grade 3 students at Madrasah Ibtidaiyah Ta'mirul Islam Surakarta in the 2023/2024 academic year. Teacher professional competence is a key factor in the learning process, especially at the Elementary School level, where basic reading, writing, and arithmetic skills are an important foundation for students' academic development. This study adopts a quantitative approach with an analytical survey method, where data in the form of numbers are collected and analyzed statistically. The study was conducted at MI Ta'mirul Islam Surakarta, Laweyan District, Central Java, from August to September 2024, with a population of 86 grade 3 students. From this population, a sample of 34 students or 40% was taken using the simple random sampling technique. Data analysis was carried out using descriptive statistics through the SPSS program, including calculating the mean, median, mode, and standard deviation. The normality test was carried out using the QQ-plot and Chi Square test to determine the data distribution, followed by hypothesis testing through correlation or regression analysis if the data met the normality assumption. The results of the study indicate that: 1) Teachers' professional competence is in two categories, namely moderate (1.4%) and high (98.6%). 2) The reading, writing and arithmetic abilities of grade 3 students are also in two categories, namely moderate (2.9%) and high (97.1%). 3) Teachers' professional competence has a significant effect on students' reading, writing and arithmetic abilities, as indicated by the sig. value of 0.004 <0.05 and t count 2.986> t table 2.000. The higher the teacher's professional competence, the better the students' reading, writing and arithmetic abilities. This study contributes to the understanding of the relationship between teacher professionalism and students' basic abilities, and can be a reference in improving the quality of education in madrasas.